Perancangan Dan Implementasi Sistem Informasi Pencatatan Penjualan Pada Mebel Cv Maju Bersama Menggunakan Metode Rapid Application Development - Ficram Marthen Luther Djawa Huky; Alfrian Carmen Talakua (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Maju Bersama is a business sector that is engaged in distributing high quality wood. Currently the business activities carried out are still conventional or still waiting for customers to come to the place of business to buy wood or when making sales reports along with end of month reports they still use a book, apart from that customers find it difficult to know what type of wood is being sold at CV Maju Together. So it requires an information system as a tool to help record sales transactions, quantity of goods, availability of goods as input materials. The development method used to design the system uses the RAD approach. The result of this research is a website-based CV Maju Bersama sales information system..